(untitled) (Research, Society and Development, 2021)
The biodiverse agroforestry systems are a soil management strategy that seeks to promote beneficial interactions between biotic and abiotic components. Pecan is a long-lived and large-sized tree species that will decisively influence the systems it integrates. The objective of this work is to establish patterns of behavior of pecan cultivars within the agroforestry system. The experiment was carried out between 2015 and 2017, the cultivar was the factor of variation evaluated, considering four treatments: ‘Barton’, ‘Cape Fear’, ‘Desirable’ and ‘Shawnee’. The variables analyzed were: plant height and diameter; number of buds per branch; number of branches; branch diameter and length; number of leaves per branch and number of branches at the end of the cycle; leaf area; number of leaflets, fresh and dry weight; number of racemes and flowers; inflorescences and ant attack and. Regarding reproductive behavior , the cultivar Barton showed protandric type dicogamy, ’Cape Fear’ oscillated the behavior, showing itself to be protogynic in the first harvest and protandrous in the following. ‘Barton’ and ‘Cape Fear’ demonstrated better reproductive performance than ‘Desirable’ and ‘Shawnee’ in agroforestry systems, however, studies that include the reproductive phase and consider other cultivars are required.